The Effect of Charismatic Client Management and Auditor's Rank on Auditor Judgment and Decision-Making Process - Behrooz Badpa; Sohrab Osta; Vahid Hasanbeigy (Pizhūhish/hā-yi ḥisābdārī-i mālī, 2022)
Some characteristics of client management can shape auditors' mentality, attitudes, and behaviors through various mechanisms, and even challenge their judgment as one of the basic pillars of an independent audit. Therefore, one of the main objectives of the present study is to investigate the effect of charismatic client management among the threats to auditor impartiality on auditor judgment and decision-making process. The other objective is to reflect on auditor's rank and organizational identity, as the factors neutralizing these threats, on auditor judgment. The trusted auditors of the Tehran Stock Exchange, including those involved in private institutions and Iran Auditing Organization, constitute the statistical population in this study, in which the data in 2020-2021 were collected using a questionnaire. The target sample consists of 170 independent auditors, and the research hypotheses were tested via the Smart PLS software. The study findings at 95% confidence interval demonstrated that charismatic client management has a significant positive effect on client identification and auditor advocacy attitude. Moreover, client identification and auditor advocacy attitude have a significant negative impact on auditor objectivity. On the other hand, auditor's rank and organizational identity improve objective judgments. Accordingly, auditors can be affected by client management even though they are not a member of their institution, but client influence is less in higher-level responsibilities of the audit firm. Thus, the results of this study can be exploited by standard developers, the Iranian Association of Certified Public Accountants, as well as independent auditors and researchers.IntroductionJudgment and decision-making have been documented as the main pillars of auditing, to the extent that auditors are always required to exploit their professional judgment and decision-making during the audit process (Khoshtinat & Bostanian, 2007). Auditors' professional judgments are often influenced by professional and constructive auditor-client relationships. In this respect, identifying the significant factors that might threaten auditors' objective judgments and then undermine their objectivity, impartiality, and independence following these relationships is so important that it has received much attention among those involved in developing standards on auditing (Ashforth et al, 2008). Some characteristics of client management can thus shape auditors' mentality, attitudes, and behaviors through various mechanisms, and even challenge their judgments. From this perspective, charismatic client management is among the major factors that make threats to auditors' impartial judgments (Akbari & Jahanshad, 2021). Therefore, the first objective of the present study is to investigate the effect of charismatic client management among the threats to auditors' impartiality on auditors' judgment and decision-making process, and the second objective is to reflect on auditors' ranks and organizational identities, as the factors neutralizing these threats, and their effects on auditors' judgments.In this regard, the general research questions addressed were as follows:Does charismatic client management have an effect on auditors' judgments through client identification?Does charismatic client management have an effect on auditors' attitudes, mentality, and behaviors toward clients?Do auditors' attitudes toward client and client identification affect auditors' judgments?Do auditors' ranks and organizational identities have a neutralizing effect on dealing with threats to auditors' objective judgments? Materials & Methods Considering its paradigm, a descriptive-correlational design was used in this applied quantitative research for data collection and analysis, based on structural equation modeling. The trusted auditors involved in private institutions and Iran Auditing Organization also constituted the statistical population in this study, and the statistical sample included 170 independent auditors, of which the data were collected through a questionnaire in 2020-21.A standardized questionnaire, in the form of open- and closed-ended items, was employed in this study. The auditor's rank was further determined using six categories, viz., 1=auditor, 2= senior auditor, 3=audit supervisor, 4=audit manager, 5=senior audit manager, and 6=audit partner. In order to evaluate auditors' objective judgments, the scenario approach centered on the Client Agreement Index by Bamber and Iyer (Bamber & Iyer, 2007) was practiced. The biggest client identification and auditor's occupational identity were also evaluated based on the Organizational Identification Scale, developed by Mael and Ashforth (Mael & Ashforth, 1992) and Bamber and Iyre (Bamber & Iyer, 2007), and the necessary revisions were made to its items with reference to the study by Svanberg, Öhman, and Neidermeyer (Svanberg et al, 2017). The given questionnaire consisted of five items and a five-point Likert-type scale. Another part of the questionnaire was related to the evaluation of auditors' advocacy attitudes, which included eight items to examine the levels of auditors' advocacy attitudes toward clients based on a five-point Likert-type scale. To measure auditors' advocacy attitudes, the scales established by Pennington et al. (Pennington et al, 2017) and Badpa and Osta (Badpa & osta, 2021) were employed. Charismatic client management was correspondingly measured by the local Charismatic Leadership Questionnaire designed by Rezaiyan et al. (Rezaeyan, et al, 2009), containing 15 items and three dimensions, i.e., environmental awareness, aligning an organization with visions, and modeling, based on a five-point Likert-type scale.  FindingOnce the measurement model of the research variables was confirmed using confirmatory factor analysis, path analysis was utilized to test the research hypotheses. The summary of the results of evaluating the structural model in this study is illustrated in the following table:Table 1: A summary of the evaluation results of the structural model of the research   Direct pathPath coefficientT Statistics (|O/STDEV|)P ValuesHypothesis testing resultsCharismatic Client Management → Client Identification0.4046.1920.000Not rejectedClient Identification → Auditor’s Client Acquiescence0.1782.4020.017Not rejectedAuditor's Organizational Identity → Auditor’s Client Acquiescence-0.3114.3770.000Not rejectedCharismatic Client Management → Auditor's Advocacy Attitude0.2132.3970.018Not rejectedAuditor's Advocacy Attitude → Auditor’s Client Acquiescence0.2163.2600.001Not rejectedAuditor's Rank  → Auditor’s Client Acquiescence-0.1822.7820.006Not rejectedSource: Research findings  Results & ConclusionBased on the results of testing the first and second research hypotheses, charismatic client management has a positive effect on client identification, and then client identification has a negative effect on auditor's objective judgment. These findings are consistent with the results reported by Svanberg et al. (Svanberg et al, 2017), Bamber and Iyer (Bamber & Iyer, 2007), and Badpa and Osta (Badpa & osta, 2021), and can be further explained based on Social Identity Theory. According to this theory, the specific characteristics of clients can directly and indirectly have a negative effect on auditors' objective judgments through client identification.Considering the results of testing the third research hypothesis, auditors' organizational identities have a positive effect on their objective judgments. With regard to the significant positive effect of organizational identity on the dimensions of professional self-doubt in independent auditing, a higher organizational identification can thus improve auditors' professional behaviors, and consequently their objective judgments (Rezaei et al, 2017). Testing the fourth and fifth research hypotheses also showed that charismatic client management has a positive effect on auditors' advocacy attitudes to clients, and such attitudes have a negative effect on their objective judgments. To elucidate these findings, it is argued that client management characteristics can influence auditors' attitudes and thinking, as the principles of organizational leadership have not considered any limits for clients' influence on the attitudes of people who are not officially employed by that organization (Badpa & osta, 2021; Akbari &  Jahanshad, 2021).In addition, auditors' advocacy attitudes toward clients and their management affect their judgments, and auditors' advocacy attitudes toward clients indicate the degree of willingness to support clients' favorable accounting procedures in the state of ambiguity (namely, contradictory evidence) (Lembke & Wilson, 1998; Kock, 2015). These findings are in line with the results reported by Badpa and Osta (Badpa & osta, 2021), Bobek, Hageman, and Hatfield (Bobek et al, 2010), Pennington et al. (Pennington et al, 2017), and Badpa et al (Badpa et al, 2019).The results of testing the final research hypothesis correspondingly demonstrated that auditors' ranks have a positive effect on their objective judgments. In other words, the higher levels of the auditing institute can make more favorable judgments than the lower levels. Putting these results in plain words, it is claimed that auditors with lower ranks have more flexibility in dealing with clients in the face of challenging situations due to various reasons, such as the lower levels of occupational (or organizational) identification and experience, and younger age. These findings are also in harmony with the results in Bamber and Iyer (Bamber & Iyer, 2007).Accordingly, auditors can be affected by client management even though they are not a member of their institution, but clients' influence is less in higher-level responsibilities of the audit firm. Thus, the study results can be exploited by the developers of standards on auditing, the Society of Certified Public Accountants, as well as independent auditors and researchers.Against this background, the effects of other dimensions of client management leadership on auditors' advocacy attitudes and the extent of their client identification, as well as the judgment and decision-making process, including initial judgment, evidence search strategy, evidence evaluation, and final judgments, can be investigated in future research.  * Corresponding author